Paciente femenino de 45 años de edad diagnosticada con hipertensión arterial que presenta obesidad tipo 2 - Santillán Herrera, Pamela Elizabeth (2020)
In the present clinical case, a 45-year-old female patient is released, residing in the city of Babahoyo, married, with a medical diagnosis of arterial hypertension and type 2 obesity. Arterial hypertension and obesity are two pathologies that usually coexist in the same patient, although they are clinically different, they are closely related to each other because both belong to the group of chronic no communicable diseases giving relation to a series of risk factors that present in common as: inappropriate habits and lifestyles related to one (intake of foods high in fat and low intake of fruits and vegetables), sedentary life, smoking, consumption of harmful substances, in addition to aging. Therefore, it is established that the objective of this clinical case is to evaluate the nutritional status and to carry out a meal plan according to the nutritional needs of the patient, in which the respective nutritional assessment, the dietary prescription, is also carried out. This provides the nutritional counseling concerned, and ends by determining the nutritional status of the patient, it also manages to intervene its comprehensive nutritional diagnosis with the following parameters: Anthropometric, biochemical, clinical and dietary evaluation, managing to act with a meal plan according to the pathologies present in the patient with an example of a menu, the respective nutritional recommendations will also be made and in each control it will be possible to show positive results in their nutritional follow-up, to achieve a healthy lifestyle through the indicators described above, thus complying with the objectives set s previously.